The efficacy and safety of isotonic and hypotonic fluids in intravenous maintenance fluid therapy in term newborns: national multicenter observational “neofluid” study - Ozkan, Hasan; Duman, Nuray; Tuzun, Funda; Narter, Fatma; Akyildiz, Can; Altuncu, Emel; Satar, Mehmet; Ozdemir, Mustafa; Kurt, Abdullah; Tugcu, Ali U.; Konak, Murat; Uygun, Saime Sundus; et al. (Frontiers in Nutrition, 2024)
The objective of this study was to evaluate the efficacy and safety of isotonic and hypotonic intravenous fluids in maintenance fluid therapy for term infants. This was a multi-centre, prospective, observational study conducted in 21 participating centres from December 30, 2020, to June 30, 2023. The study included term newborns requiring parenteral fluid therapy for maintenance (NCT04781361). The fluid treatment was divided into two groups based on the concentration of sodium in the parenteral fluid, designated as hypotonic (NaCl < 130 mmol/L) and isotonic (NaCl = 130–154 mmol/L). The primary outcomes were the change in mean plasma sodium (pNa) levels per hour (∆pNa mmol/L/hour), the incidence of hyponatremia (pNa <135 mmol/L) and hypernatremia (pNa >145 mmol/L), and the occurrence of clinically significant changes in sodium levels (∆pNa >0.5 mmol/L/hour). A total of 420 patients from 21 centers were included. The ∆pNa was negative in the hypotonic fluid group and positive in the isotonic fluid group, with a significant difference between the groups [respectively -0.07 ± 0.03 (95% CI: -0.13 to -0.02); 0.04±0.03 (95%CI: -0.02 to 0.09), p=0.04]. There was no difference between the groups in terms of the development of hypernatremia or a clinically meaningful pNa increase. The hypotonic fluid group had a higher incidence of hyponatremia and a clinically meaningful sodium decrease compared to the isotonic fluid group [7.9% vs. 1.2% (OR:6.5, p:0.03)] and [12.2% vs.4.2% (OR:2.9, p=0.03)]. Contrary to current understanding, this large-scale study is the first to demonstrate that the use of hypotonic fluids in maintenance fluid therapy for newborns poses a risk of hyponatremia development, whereas isotonic fluid therapy appears safe.